Aspects of Capital Investment in Great Britain 1750-1850 : A preliminary survey, report of a conference held the University of Sheffield, 5-7 January 1969 /: A preliminary survey, report of a conference held the University of Sheffield, 5-7 January 1969. (2013) - Unknown
No abstract available